2017
DOI: 10.1038/s41598-017-03361-0
|View full text |Cite
|
Sign up to set email alerts
|

RIM1/2 in retinal ganglion cells are required for the refinement of ipsilateral axons and eye-specific segregation

Abstract: Neural activity is crucial for the refinement of neuronal connections during development, but the contribution of synaptic release mechanisms is not known. In the mammalian retina, spontaneous neural activity controls the refinement of retinal projections to the dorsal lateral geniculate nucleus (dLGN) and the superior colliculus (SC) to form appropriate topographic and eye-specific maps. To evaluate the role of synaptic release, the rab-interacting molecules (RIMs), a family of active zone proteins that play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…In the CasRx-treated NMDA-injured retina, we observed a large amount of tdTomato + axons in the treated retina and the optic nerve, but no such axons in control AAV-treated group (Figures 4B and 4C). Remarkably, we found tdTomato + axons in the dLGN and SC, which were much more abundant in the contralateral than the ipsilateral side of the brain (Figures 4D and 4E), consistent with expectation that newly formed axon projections of the converted RGCs correctly send their projections to their central target areas (Assali et al, 2017;Rebsam et al, 2009).…”
Section: Central Projections Of Converted Rgcs Restored Visual Responsessupporting
confidence: 89%
“…In the CasRx-treated NMDA-injured retina, we observed a large amount of tdTomato + axons in the treated retina and the optic nerve, but no such axons in control AAV-treated group (Figures 4B and 4C). Remarkably, we found tdTomato + axons in the dLGN and SC, which were much more abundant in the contralateral than the ipsilateral side of the brain (Figures 4D and 4E), consistent with expectation that newly formed axon projections of the converted RGCs correctly send their projections to their central target areas (Assali et al, 2017;Rebsam et al, 2009).…”
Section: Central Projections Of Converted Rgcs Restored Visual Responsessupporting
confidence: 89%
“…Among these genes, we found Pcdh9 (Martersteck et al, 2017), Slc6a4 (Koch et al, 2011) and Prdm16 (Groman-Lupa et al, 2017). Their expression may be more restricted later on during RGC development (Pcdh9), or expand to other RGC cell types (Slc6a4; (Assali et al, 2017)). This latter gene is specific to the RGCs that will send their axon to the ipsilateral side of the brain (Koch et al, 2011;Peng et al, 2018).…”
Section: Transcriptional Waves Drive Retinal Ganglion Cell Differentimentioning
confidence: 82%
“…In the developing retina, ISH studies have demonstrated that SLC6A4 is transcribed transiently in retinal ganglion cells (Upton et al 1999; GarcĂ­a-Frigola and Herrera 2010). Furthermore, a SLC6A4 -cre mouse strain showed recombination in retinal ganglion cells (Assali et al 2017). Several diseases are associated with SLC6A4 , including obsessive-compulsive disorder (Sinopoli et al 2017), anxiety (Arias et al 2012), and post-traumatic stress disorder, as well as depression-susceptibility in people experiencing emotional trauma (Kuzelova et al 2010).…”
Section: Resultsmentioning
confidence: 99%